2019
DOI: 10.1177/0885328219863291
|View full text |Cite
|
Sign up to set email alerts
|

Mucopenetrating lipoplexes modified with PEG and hyaluronic acid for CD44-targeted local siRNA delivery to the lungs

Abstract: RNA interfering technology has become a successful strategy for targeted gene silencing through the use of efficient delivery systems. A nanocarrier must be especially designed when considering unusual routes due to RNA instability in biological medium. Lung delivery provides extensive area of absorption and alveolar deposition, non-invasiveness and local action. However, biological barriers such as lung mucus are a great challenge to the efficient delivery of nanocarriers for therapeutic purpose. Here, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Following treatment with LIP, LIP-HA4800 and LIP-HA14800, we demonstrated that HA14800 increased the diffusion efficiency of liposomes in contrast to HA4800 (Figure 3). To the best of our knowledge, in the literature there are studies analyzing mucus penetrating ability of nanovehicles, correlating this activity to surface charge and to MW of polyethylene glycol (PEG) coating [31,32,33]. Very recently a research group modified lipoplexes (LX) for siRNA delivery to the lung with PEG and HA and demonstrated that non-PEGylated HA-LX diffused comparably to PEGylated LX, in contrast to non-modified LX, which remained entrapped in the mucus [33].…”
Section: Discussionmentioning
confidence: 99%
“…Following treatment with LIP, LIP-HA4800 and LIP-HA14800, we demonstrated that HA14800 increased the diffusion efficiency of liposomes in contrast to HA4800 (Figure 3). To the best of our knowledge, in the literature there are studies analyzing mucus penetrating ability of nanovehicles, correlating this activity to surface charge and to MW of polyethylene glycol (PEG) coating [31,32,33]. Very recently a research group modified lipoplexes (LX) for siRNA delivery to the lung with PEG and HA and demonstrated that non-PEGylated HA-LX diffused comparably to PEGylated LX, in contrast to non-modified LX, which remained entrapped in the mucus [33].…”
Section: Discussionmentioning
confidence: 99%
“…Materials that change in response to acidic conditions and have a proton sponge effect have been investigated to aid in endosomal escape, enabling NPs to avoid degradation 40,169,173 . LNPs, which include cationic and ionizable materials, are good examples of these intracellularly triggered delivery mechanisms and are often used to carry nucleic acids into cells 3,[174][175][176][177][178][179] . Materials can respond to the acidic endosomal pH, but NPs have also been designed to react to the reductive endosomal environment 180,181 .…”
Section: Cellular and Intracellular Barriersmentioning
confidence: 99%
“…However, mucus can be highly variable between patients, and existing murine models may not accurately mimic the thickened airway mucus produced by patients with cystic fibrosis 283 . Other existing methods for improving mucosal delivery include the incorporation of muco-penetrating lipoplexes 176 , mucolytic proteins 149 , thiolated hyaluronic acid coatings 48 and N-acetylcysteine 137 . All of these methods attempt to improve the transversal of mucosal barriers by altering NP surface properties 118 .…”
Section: Nps For Genome Editingmentioning
confidence: 99%
“…sugars, peptides, proteins, or aptamers to actively target receptors overexpressed on specific cells such as cancer, endothelial or immune cells [20,21]. In the last decade, several teams, including our laboratory, have developed an array of surface coating strategies to target the CD44 receptor that is overexpressed by several key cell types, including cancer stem cells and activated pro-inflammatory M1 macrophages [21][22][23]. Successful anti-CD44 ligands include antibodies [24], aptamers [23] as well as hyaluronic acids (HA) [25], which is the natural ligand of the CD44 receptor.…”
Section: Introductionmentioning
confidence: 99%